Information quality requirements for a nutrition app based on experts interviews - Mohammed, Siti Asma; Mohamed, Aden Ighe; Nordin, Azlin (2021)
Many people nowadays are using nutrition and dietary apps to manage their health by monitoring their food and calorie intake. Online health information enables people to search for specific health-related information that may concern them in the comfort and privacy of their home. Thus, the quality of such information is crucial to ensure people are getting the right and reliable information. The objective of this paper is to present the information quality requirements for nutrition app by analysis of experts’ interviews. The interview was conducted using semi structured interview with five nutritionists. The finding from the interviews show that a nutrition app should include a complete, reliable, accurate and updated information.